Sosialisasi Penerapan Strategi Concept Song dalam Meningkatkan Motivasi Belajar Anak di Desa Jayaraksa Kabupaten Ciamis - Robi, Yelia Ahya; Nurwahidah, Ai Linda; Ratnasari, Ani; Huda, Bela Salsabila; Awaliah, Ira Ro’fatul; Fuadah, Pupu Samrotul; A’ini, Siti Nurul (Lembaga Pengabdian kepada Masyarakat (LPkM) Universitas Islam Darussalam (UID) | Islamic University of Darussalam Ciamis-Jawa Barat, 2022)
The implementation of the Concept Song strategy as an alternative teaching method has become an important consideration to enhance students' learning motivation. The aim of this research is to evaluate the use of the Concept Song strategy as an alternative in teaching that can improve students' learning motivation in Jayaraksa Village. The research method used is classroom action research involving students at the Diniyah Takmiliyah Awaliyah (DTA) level and Early Childhood Education (PAUD). This research was conducted in two cycles, with each cycle consisting of planning, implementation, observation, and reflection. The research findings indicate that the implementation of the Concept Song strategy provides a positive contribution in enhancing students' learning motivation. In the first cycle, there was a 20% increase in students' learning motivation, and in the second cycle, there was a 35% increase. This is evidenced by students' active participation in learning, their involvement in singing songs, and their enthusiasm in understanding the concepts of the subjects. In the process of implementing the Concept Song strategy, teachers use songs that are relevant to the concepts being taught. These songs are tailored to students' understanding and needs, thereby stimulating their interest and learning motivation. Additionally, students are given the opportunity to be creative in creating lyrics related to the lesson material, which makes them feel more engaged in the learning process. In conclusion, it can be inferred that the use of the Concept Song strategy is an effective alternative for enhancing students' learning motivation in Jayaraksa Village. This strategy successfully creates a more interactive, enjoyable, and motivating learning environment for students to actively engage in the learning process. This research is expected to contribute positively to the development of innovative teaching methods and the improvement of students' learning motivation.